2019
DOI: 10.3390/condmat4020050
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon Resonance (SPR) to Magneto-Optic SPR

Abstract: In this editorial, a brief background of the surface plasmon resonance (SPR) principle is discussed, followed by several aspects of magneto-optic SPR (MOSPR) and sensing schemes from the viewpoint of fundamental studies and potential technological applications. New sensitivity metrics are introduced that would allow researchers to compare the performance of SPR and MOSPR-based sensors. Merits of MOSPR over SPR based sensors and challenges faced by MOSPR sensors in terms of their practical use and portability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Here, we investigate the sensitivity with respect to the temperature change (not to the refractive index one at optical frequencies). 19 The sensitivity is defined as Δf/ΔK where Δf is the frequency shift and ΔK is the temperature one. 12 In Figure 3, a high sensitivity of 2.63 × 10 −2 THz/K is successfully achieved, which is more than three times as large as that of the conventional waveguide sensor, for example, F I G U R E 1 Configuration of a Kretschmann-type waveguide sensor [Color figure can be viewed at wileyonlinelibrary.com] 7.5 × 10 −3 THz/K 12 and 6.6 × 10 −3 THz/K.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we investigate the sensitivity with respect to the temperature change (not to the refractive index one at optical frequencies). 19 The sensitivity is defined as Δf/ΔK where Δf is the frequency shift and ΔK is the temperature one. 12 In Figure 3, a high sensitivity of 2.63 × 10 −2 THz/K is successfully achieved, which is more than three times as large as that of the conventional waveguide sensor, for example, F I G U R E 1 Configuration of a Kretschmann-type waveguide sensor [Color figure can be viewed at wileyonlinelibrary.com] 7.5 × 10 −3 THz/K 12 and 6.6 × 10 −3 THz/K.…”
Section: Discussionmentioning
confidence: 99%
“…We further discuss the temperature characteristics in Figure 3, in which the temperature is varied from 280 to 320 K. It is found that the frequency dip shifts towards higher frequencies as the temperature is increased. Here, we investigate the sensitivity with respect to the temperature change (not to the refractive index one at optical frequencies) 19 . The sensitivity is defined as Δ f /Δ K where Δ f is the frequency shift and Δ K is the temperature one 12 .…”
Section: Discussionmentioning
confidence: 99%
“…They also allow amplified sensitivity and improved detection limit, as high as 2 × 10 −8 RIU for bilayer or bilayer/multilayers when combined with a PC 46. 181 Thus, it offers many adjustments possible to optimize sensor performance.…”
Section: Toward Industrial Applicationsmentioning
confidence: 99%
“…We can also theoretically calculate the sensitivity as the wavelength shift of per refractive index unit (RIU) for each WCSPR mode as shown in Fig. 7, according to the sensitivity definition in references [20], [21]. When the sensor was used for detecting the test medium with a relatively higher refractive index, the sensitivity will increase dramatically.…”
Section: The Sensitivity Of Fiber Waveguide Coupled Spr Sensormentioning
confidence: 99%